The current status, challenges, and future perspectives for managing diseases of brassicas - Greer, Shannon F.; Surendran, Arthy; Grant, Murray; Lillywhite, Robert (Frontiers in Microbiology, 2023)
The Brassica genus comprises the greatest diversity of agriculturally important crops. Several species from this genus are grown as vegetable and oil crops for food, animal feed and industrial purposes. In particular, B. oleracea has been extensively bred to give rise to several familiar vegetables (cabbage, broccoli, cauliflower, kale and Brussels Sprouts, etc.) that are grouped under seven major cultivars. In 2020, 96.4 million tonnes of vegetable brassicas were produced globally with a 10.6% increase over the past decade. Yet, like other crops, the production of brassicas is challenged by diseases among which, black rot, turnip yellows virus, clubroot and downy mildew have been identified by growers as the most damaging to UK production. In some cases, yield losses can reach 90% depending upon the geographic location of cultivation. This review aims to provide an overview of the key diseases of brassicas and their management practices, with respect to the biology and lifecycle of the causal pathogens. In addition, the existing controls on the market as well as those that are currently in the research and development phases were critically reviewed. There is not one specific control method that is effective against all the diseases. Generally, cultural practices prevent disease rather than reduce or eliminate disease. Chemical controls are limited, have broad-spectrum activity, are damaging to the environment and are rapidly becoming ineffective due to the evolution of resistance mechanisms by the pathogens. It is therefore important to develop integrated pest management (IPM) strategies that are tailored to geographic locations. Several knowledge gaps have been identified and listed in this review along with the future recommendations to control these four major diseases of brassicas. As such, this review paper will act as a guide to sustainably tackle pre-harvest diseases in Brassica crops to reduce food loss.